The Effect Of Mind Mapping On Students’ Ability In Writing Descriptive Texts At Grade Vii Of SMP Swasta Cinta Rakyat 3 Pematangsiantar - Miranda Kristin Lumban Tungkup; Selviana Napitupulu (Jurnal Ilmu Pendidikan dan Sosial, 2026)
of seventh grade students in writing descriptive texts at SMP Swasta Cinta Rakyat 3 Pematangsiantar. Writing descriptive texts is a challenging skill for junior high school students, especially in organizing ideas coherently and logically. Many students have difficulty in maintaining a clear flow of ideas, connecting one sentence to another, and developing descriptions in an organized manner so that the resulting writing often appears fragmented and less integrated. This condition indicates the need for effective teaching techniques to help students organize their thoughts before writing. The method used in this study is a quantitative method with a quasi-experimental design involving two groups, namely the experimental group and the control group. The study population was all seventh grade students of SMP Swasta Cinta Rakyat 3 Pematangsiantar, with a sample of 60 students selected using a purposive sampling technique, 30 students each in the experimental group and the control group. Data were collected through writing tests in the form of pre-tests and post-tests, then analyzed using descriptive statistics and t-tests. The results showed that the coherence scores of students in the experimental group were higher than those in the control group. The t-test results show that the calculated t-value is greater than the t-table at a significance level of 5% (t = 4.86; p < 0.05). Based on these findings, it can be concluded that the Mind Mapping Technique has a positive and significant effect on students' coherence in writing descriptive texts. Practically, the results of this study can serve as a reference for English teachers in implementing effective instructional strategies to improve students’ writing skills and encourage them to organize their ideas more systematically, as well as provide useful references for future researchers in conducting more in-depth studies related to writing instruction.